Falling behind the Rest?: China and the Gender Gap Index - Chen, Binli (Social Inclusion, 2020)
China’s rank falling in the Global Gender Gap Index of the World Economic Forum has aroused the domestic scholar’s controversy. Based on the data provided by the Global Gender Gap Report, this article will describe the gender inequality in China by comparing its overall index scores and scores in the fields of economic participation and opportunity, education attainment, health and survival, and political empowerment with other countries, and then examining the reasons for China’s falling in rank through the score changes of sub-dimensions and indicators. Analysis of the data suggests that China has not kept up with the rate of improvement in the overall index, and in the four fields, compared to the original 112 countries, the upper-middle income countries, and the Asian and Pacific countries. Over the 13 years covered by the report, China’s score experienced a rapid improvement from 2006 to 2009 and a decline after 2013. China’s high sex ratio at birth, further expansion of gender inequality in active life expectancy, and an enlarged gender gap in secondary education caused China’s lagging overall score and ranking. In addition, the inclusion of measures such as secondary education enrollment, political empowerment, and other indicators also led to the backward ranking of China to some extent.